2014
DOI: 10.1073/pnas.1323586111
|View full text |Cite
|
Sign up to set email alerts
|

The habenula encodes negative motivational value associated with primary punishment in humans

Abstract: Learning what to approach, and what to avoid, involves assigning value to environmental cues that predict positive and negative events. Studies in animals indicate that the lateral habenula encodes the previously learned negative motivational value of stimuli. However, involvement of the habenula in dynamic trialby-trial aversive learning has not been assessed, and the functional role of this structure in humans remains poorly characterized, in part, due to its small size. Using high-resolution functional neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
110
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(132 citation statements)
references
References 45 publications
18
110
0
Order By: Relevance
“…Greater left habenula activation to the receipt of punishment relative to reward in healthy controls was identified, consistent with previous reports that the habenula conveys a negative reward signal during associative learning in humans (Lawson et al, 2014). This result is also consistent with findings in monkeys Hikosaka, 2007, 2009a).…”
Section: Blunted Habenula Activation In Depression During Punishment supporting
confidence: 91%
See 1 more Smart Citation
“…Greater left habenula activation to the receipt of punishment relative to reward in healthy controls was identified, consistent with previous reports that the habenula conveys a negative reward signal during associative learning in humans (Lawson et al, 2014). This result is also consistent with findings in monkeys Hikosaka, 2007, 2009a).…”
Section: Blunted Habenula Activation In Depression During Punishment supporting
confidence: 91%
“…Two studies reported that patients with major depression exhibited increased metabolic activity in the vicinity of the habenula during tryptophan depletion, measured during the resting state (Morris et al, 1999;Roiser et al, 2009). Habenula activation to aversive stimuli (cues associated with electric shocks) has recently been reported in healthy individuals with highresolution functional magnetic resonance imaging (fMRI) (Lawson et al, 2014;Hennigan et al, 2015) and habenula activation to negative feedback was reported in an earlier study, though using lower resolution image acquisition (Ullsperger and von Cramon, 2003). However, attenuated habenula activation was observed in patients with depression in two recent studies (Furman and Gotlib, 2016;Lawson et al, 2016), which is inconsistent with predictions from contemporary theories of its role in depression (Shumake and GonzalezLima, 2013;Proulx et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These phenotypes are not restricted to zebrafish: Lat À/À mice also show alterations in several brain regions including cortex and habenula, a structure that plays a central role in the positive and negative reinforcements of the reward process. [51][52][53] Cd247 À/À mice show brain morphological defects, in particular reduced glutamatergic synaptic activity in the retina 54 and synaptic plasticity in the hippocampus, 41 as well as impaired learning and memory, a T cell-independent mechanism. 44 In zebrafish, ZAP70 is expressed ubiquitously in early development, and highly and specifically in the head from the 16-somite stage, with low expression level throughout the rest of the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies implicate the LHb in processing aversive or punishing signals, such as error detection (Li et al, 2008) or aversive electric shock (Hennigan et al, 2015;Lawson et al, 2014). Such studies also demonstrate a feed-forward influence of the habenula on VTA/SN activity (Ide and Li, 2011).…”
Section: The Impact Of Cocaine On the Hedonic Experience Of Non-drug mentioning
confidence: 98%